2019
DOI: 10.1007/s10068-018-00549-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volatile profiles in Fagopyrum esculentum (buckwheat) soksungjang prepared with different starter cultures during fermentation

Abstract: This study investigated the differences and changes in the volatile profiles of buckwheat soksungjang (BS) inoculated with multiple microbial starters (Lactobacillus brevis ? Aspergillus oryzae, BS-LA vs. Lactobacillus brevis ? Bacillus amyloliquefaciens, BS-LB) during fermentation using SPME coupled with GC-MS and partial least square-discriminant analysis. BS samples fermented for 5 weeks could be differentiated from other BS samples with shorter fermentation periods, and the BS-LA and BS-LB samples fermente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Phytol (1TMS), D-ribitol (5TMS), 1,2,3,4-tetrakis[(trimethylsilyl)ox y]-butane and 2,3-bis(trimethylsilyl)-butane were identified in cheonggukjang (Kim et al, 2012). Studies on soksungjang revealed that several alcohols, carbonyls, ketones, esters, benzene and derivatives, furan and derivatives and aliphatic hydrocarbons constituted the volatile compounds (Park et al, 2017(Park et al, , 2019. Alcohols, carbonyls, ketones, esters, aliphatic hydrocarbons, benzenes and 2-pentylfuran (furans) were found in fermented soybean products (Jeong et al, 2017(Jeong et al, , 2019Park & Kim, 2020).…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytol (1TMS), D-ribitol (5TMS), 1,2,3,4-tetrakis[(trimethylsilyl)ox y]-butane and 2,3-bis(trimethylsilyl)-butane were identified in cheonggukjang (Kim et al, 2012). Studies on soksungjang revealed that several alcohols, carbonyls, ketones, esters, benzene and derivatives, furan and derivatives and aliphatic hydrocarbons constituted the volatile compounds (Park et al, 2017(Park et al, , 2019. Alcohols, carbonyls, ketones, esters, aliphatic hydrocarbons, benzenes and 2-pentylfuran (furans) were found in fermented soybean products (Jeong et al, 2017(Jeong et al, , 2019Park & Kim, 2020).…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…Alcohols, carbonyls, ketones, esters, aliphatic hydrocarbons, benzenes and 2-pentylfuran (furans) were found in fermented soybean products (Jeong et al, 2017(Jeong et al, , 2019Park & Kim, 2020). Overall, microorganisms involved the fermentation process typically elevate the volatile compounds profile in fermented soybeans through various complex metabolism processes (glycolysis, lipolysis, and pyruvate and proteolytic), however, the benzenes production originated from phenylalanine catabolism, which could vary with the type and level of activity of enzymes produced by the microorganisms (Park et al, 2019).…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on soksungjang have compared the metabolite profile of buckwheat soksungjang samples (BSs) obtained via traditional and commercially modified methods or inoculated with multiple microbial starters (Park et al ., 2017; Park et al ., 2019). Based on the fermentation type and fermentation period, accelerated changes and differences in the volatile compounds of commercial BSs were reported compared to the traditional type (Park et al ., 2017).…”
Section: Gc‐ms‐based Metabolomics Of Clffsmentioning
confidence: 99%
“…Based on the fermentation type and fermentation period, accelerated changes and differences in the volatile compounds of commercial BSs were reported compared to the traditional type (Park et al ., 2017). In a follow‐up study, variations in the volatile profile of BSs (mainly, acids, benzenes and esters) were found to depend on the microbial starter combinations as well as fermentation periods (Park et al ., 2019). These findings may provide insight for optimising the fermentation process of BS.…”
Section: Gc‐ms‐based Metabolomics Of Clffsmentioning
confidence: 99%